(untitled) (Bangladesh Journal of Physics, 2025)
The Ni0.5Mg0.5CdxFe2-xO4 ferrites (x = 0.00, 0.02, 0.04, 0.06, 0.08, and 0.10) were prepared by the solid-state reaction method using laboratory-grade oxide materials. Samples from each composition were prepared and then sintered at 1000 °C for 3 hours. The Cd-doped Ni-Mg ferrites’ structural and surface morphology effects were analyzed by XRD and SEM. XRD analysis indicated that all the sintered samples crystallized in a single-phase cubic spinel structure. It follows from Vegard’s law that, in Ni-Mg-Cd ferrites, the lattice parameter increased linearly with the substitution of Fe³⁺ ions by Cd²⁺. In all the samples, the theoretical density was higher than their bulk densities due to the pores present in them, as the sintering temperature is influenced. SEM images showed that the Cd-doped Ni-Mg ferrites significantly modified the average grain size; thus, the surface morphology appeared to be homogeneous and consisted of well-defined spherical grains. The average grain size decreased while doping with Cd²⁺ in Ni0.5Mg0.5CdxFe2-xO4 up to x = 0.08 and then increased with a further increase in doping concentration. No significant effect on Ms, Hc, and Mr was observed while measuring from the M-H curve by VSM and hysteresis loops. The coercive value Hc was very low, and hence Ni-Mg-Cd ferrites belong to the family of soft ferrites. The Ms value increased in all samples with the content of Cd doping. With these results, it can be asserted that the addition of Cd can make Ni-Mg ferrites more magnetic at the core and change their structure, along with surface appearance; thus, these materials will be useful in many magnetic applications. Bangladesh Journal of Physics, 28(1), 51-58, June 2021